Traumatic Rupture of the Pericardium: Report of Two Cases with Unusual Features - Rubio-Alvarez, J. (1983)
We describe two cases of traumatic rupture of the pericardium with unusual features. The first patient had isolated pericardial rupture with extrapericardial luxation of the heart, and the sound patient had a combined rupture of the pericardium and diaphragm, with prolapsing bowel into the pericardial cavity. After emergency operation, both patients recovered uneventfully.